Water circulation, and not ocean acidification, affects coral recruitment and survival at shallow hydrothermal vents. (5th February 2019) - Oprandi, Alice; Montefalcone, Monica; Morri, Carla; Benelli, Fabio; Bianchi, Carlo Nike
Abstract: Shallow hydrothermal vents emit warm water, carbon dioxide, toxic chemicals, nutrients and reduced compounds that altogether mimic climate and human impacts, and are therefore considered as 'natural laboratories' at which can be investigated the effects of these stressors on marine ecosystems. One of the effects more thoroughly investigated is the impact of reduced pH on marine biodiversity. Calcifying organisms, such as corals, are expected to be more affected, but their response to reduced pH values in seawater has been tackled mostly by laboratory studies. Here, we assessed coral recruitment and juvenile survival, two fundamental processes for coral reef maintenance and resilience, in shallow reefs of North Sulawesi (Indonesia) close to hydrothermal vents. Differences in abundance of coral recruits (<5 cm in diameter) and juveniles (5–15 cm in diameter) were evaluated at vent sites and at control sites, on both reef flats and upper slopes. Recruits of Acropora and other broadcasting corals resulted more abundant near vents, while no difference in juvenile survival was observed between vent sites and controls. On the contrary, Pocillopora, which includes many brooders, showed a low density of recruits and low survival rates at vent sites. Vents caused a typical closed water circulation that retained coral larvae on site, and this effect, rather than water acidification or the emission of chemical compounds, was likely to be responsible for increased recruitment of broadcasters. Graphical abstract: Highlights: Coral recruitment and survival are not affected by water acidification. Recruits' abundance is enhanced in vent sites compare to control sites. Hydrothermal vent cause a closed water circulation. Vent activity promote coral recruitment by retaining coral larvae. Broadcast-spawning corals, Acropora and most of the Others, seem to be favoured.